2006
DOI: 10.1073/pnas.0511021103
|View full text |Cite
|
Sign up to set email alerts
|

ChiralN-salicylidene vanadyl carboxylate-catalyzed enantioselective aerobic oxidation of α-hydroxy esters and amides

Abstract: A series of chiral vanadyl carboxylates derived from N-salicylidene-L-␣-amino acids and vanadyl sulfate has been developed. These configurationally well defined complexes were examined for the kinetic resolution of double-and mono-activated 2°alcohols. The best chiral templates involve the combination of L-tert-leucine and 3,5-di-t-butyl-, 3,5-diphenyl-, or 3,4-dibromo-salicylaldehyde. The resulting vanadyl(V)-methoxide complexes after recrystallization from air-saturated methanol serve as highly enantioselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…[5] Despite the advances made in these asymmetric reactions, kinetic resolution (KR) [6] of racemic a-hydroxy esters is still one of the most important and reliable ways to acquire one isomer in an enantiomerically pure form. Two routes are usually employed in the KR of a-hydroxy esters: oxidative KR [7] and acylative KR [8] (Scheme 1). Chiral transition-metal-complex-catalyzed asymmetric aerobic oxidations transfer one isomer of a-hydroxy esters into a-ketoesters, therefore another unreacted isomer can be reversed enantioselectively.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Despite the advances made in these asymmetric reactions, kinetic resolution (KR) [6] of racemic a-hydroxy esters is still one of the most important and reliable ways to acquire one isomer in an enantiomerically pure form. Two routes are usually employed in the KR of a-hydroxy esters: oxidative KR [7] and acylative KR [8] (Scheme 1). Chiral transition-metal-complex-catalyzed asymmetric aerobic oxidations transfer one isomer of a-hydroxy esters into a-ketoesters, therefore another unreacted isomer can be reversed enantioselectively.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Chen et al developed a series of chiral N -salicylidene vanadyl carboxylate complexes to perform catalytic kinetic resolution of α-hydroxycarboxylic esters, thioesters, amides ( Weng et al, 2006 ; Chen et al, 2007 ; Salunke et al, 2011 ) and α-hydroxyketones ( Chen et al, 2011 ) by using molecular oxygen as the terminal oxidant at ambient conditions. It was found that aerobic oxidation of ( S )-alcohols proceeds more readily than their ( R )-counterparts in the presence of vanadium complex 12 and its congeners ( Scheme 4 ).…”
Section: Transition Metal-catalyzed Transformationsmentioning
confidence: 99%
“…It was found that aerobic oxidation of ( S )-alcohols proceeds more readily than their ( R )-counterparts in the presence of vanadium complex 12 and its congeners ( Scheme 4 ). As a notable example illustrating high oxidation selectivity, ( R )-isomer of N -benzylamide 13 was obtained in 50% yield and 98% ee ( Weng et al, 2006 ). Drastically slower rate of the oxidation for ( R )-isomer ( k rel = 458) was rationalized based on the results of single crystal X-ray analysis of the corresponding catalyst-substrate adduct 14 .…”
Section: Transition Metal-catalyzed Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordination complexes and some of their applications continue to be reported by many groups, and include salen-type complexes (e.g. 19,66,[171][172][173][174][175][176], pyrone, pyridinone and pyrimidinone complexes (177)(178)(179), several types of Schiff bases and related complexes (66, [180][181][182], picolinato (e.g. 183), quinoline derivatives (184) dipicolinato complexes (185), compounds involving ligands such as amino acids or derivatives (28,(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197), hydroxycarboxylates (198,199), but novel classes of coordination compounds and other new reports on previously known compounds are too many to name.…”
Section: Coordination Chemistrymentioning
confidence: 99%